The Discounts, Free Shipping, Trust and Consumer Assessment Ratings on Product Purchasing Decisions on The Shopee Application - Wahyuni, Dewi; Nasution, Ade Parlaungan; Hutagaol, Anita Sri Rejeki (Social Sciences Insights Journal, 2024)
E-commerce Shopee is one of the E-commerce in Indonesia which has a positive trend as the leader of the Indonesian marketplace. This study aims to determine how much influence discounts, free shipping, trust and consumer assessment ratings have on purchasing decisions for cosmetic products on Shopee application users by taking the research subject of the Labuhanbatu Regency community. The research method used is quantitative research and the data collection method used in this study is by distributing questionnaires in which there are questionnaires distributed to respondents. The sample in this study amounted to 150 respondents who used the shopee application with a distribution period of 3 months. The sampling technique used purposive sampling and data analysis techniques smartPLS 4.0 software model. The findings that respondents who buy or shop at E-commerce Shopee are respondents who have high motivation due to the age and education of respondents who are good enough to have experience shopping online at E-commerce Shopee. The results of hypothesis testing show that the variables of discounts, free shipping, trust and consumer assessment ratings are able to directly influence consumer decisions to shop at E-commerce Shopee.